Efficacy and safety of Velmanase alfa in the treatment of patients with alpha‐mannosidosis: results from the core and extension phase analysis of a phase III multicentre, double‐blind, randomised, placebo‐controlled trial. Issue 6 (30th May 2018) - Borgwardt, Line; Guffon, Nathalie; Amraoui, Yasmina; Dali, Christine I.; De Meirleir, Linda; Gil‐Campos, Mercedes; Heron, Bénédicte; Geraci, Silvia; Ardigò, Diego; Cattaneo, Federica; Fogh, Jens; Van den Hout, J. M. Hannerieke; et al.
Abstract: Introduction: This phase III, double‐blind, randomised, placebo‐controlled trial (and extension phase) was designed to assess the efficacy and safety of velmanase alfa (VA) in alpha‐mannosidosis (AM) patients. Methods: Twenty‐five patients were randomised to weekly 1 mg/kg VA or placebo for 52 weeks. At study conclusion, placebo patients switched to VA; 23 patients continued receiving VA in compassionate‐use/follow‐on studies and were evaluated in the extension phase [last observation (LO)]. Co‐primary endpoints were changes in serum oligosaccharide (S‐oligo) and in the 3‐min stair‐climb test (3MSCT). Results: Mean relative change in S‐oligo in the VA arm was −77.6% [95% confidence interval (CI) −81.6 to −72.8] at week 52 and −62.9% (95% CI −85.8 to −40.0) at LO; mean relative change in the placebo arm was −24.1% (95% CI −40.3 to −3.6) at week 52 and −55.7% (95% CI −76.4 to −34.9) at LO after switch to active treatment. Mean relative change in 3MSCT at week 52 was −1.1% (95% CI −9.0 to 7.6) and − % (95% CI −13.4 to 6.5) for VA and placebo, respectively. At LO, the mean relative change was 3.9% (95% CI −5.5 to 13.2) in the VA arm and 9.0% (95% CI −10.3 to 28.3) in placebo patients after switch to active treatment. Similar improvement pattern was observed in secondary parameters. A post hoc analysis investigated whether some factors at baseline could account for treatment outcome; none of those factors were predictive of the response to VA, besides age. Conclusions: These findings support the utility of VA for the treatment of AM, with more evident benefit over time and when treatment is started in the paediatric age.